IMPOR BARANG LUAR NEGERI DALAM PRAKTIK JASA TITIP ONLINE BERDASARKAN PERATURAN MENTERI KEUANGAN NOMOR 203/PMK.04/2017 - Muhammad Darwis; M Alpi Syahrin; Muhammad Farhan Wiliaziz (Yayasan Lembaga Pendidikan Asas, 2023)
Jastip actors avoid the obligation to pay Import Duty and Tax in the Context of Import so that they are considered detrimental to the domestic industry because they sell goods at low prices. The Jastip perpetrators used the splitting method, namely dividing goods ordered by entrusted to certain people in one group. If this is always done, it will have an impact on domestic business actors of the Republic of Indonesia. This type of sociological legal research uses an empirical juridical approach using data sources of primary legal materials, secondary legal materials and tertiary legal materials. Implementation regarding Domestic Imports in the practice of online delivery services besides using PMK Number 203/PMK.04/2017 and PMK Number 199/PMK.010/2019, but also using a system from Customs and also using BTKI as a guideline based on Risk Management . There are several problem factors, namely the ignorance of the public about the latest regulations related to BM and PDRI and related to the provisions on Import of consigned goods, several reasons for the public to avoid paying Import Duty and Tax in the Context of Import, namely using vouchers, discounts and also using consignment reasons. is based on the results of the giveaway where the reason is not justified by the provisions of the applicable laws and regulations.